Arteriovenous fistula between descending aorta and left inferior pulmonary vein: Closure with vascular plugs - Mustafa Kösecik (Türk Kardiyoloji Derneği Arşivi, 2016)
Echocardiography revealed systemic artery to pulmonary venous fistula, a rare vascular anomaly, in a 20-month-old girl, and multislice computed tomography angiography (CTA) was performed to rule out congenital heart disease. Normal bronchial connection and pulmonary vasculature were observed in the lung. The fistula drained through the left inferior pulmonary vein to the left atrium leading to a left-to-left shunt. Percutaneous intervention was performed in 2 stages using Amplatzer vascular plugs to close successfully.